Інноваційні агроструктури Дніпропетровщини - Мельник, Леонід Юхимович; Melnick, Leonid; Климова, О. С.; Klimova, O. (Дніпропетровський державний аграрний університет, 2009)
Проведено класифікацію аграрних підприємств за критерієм рівня їх техніко-технологічної оснащеності. Виділено групу інноваційних. Визначено місце і роль цієї групи підприємств в аграрному секторі Дніпропетровської області. The agrarian enterprises classification for criteria of level of their engineering and technology equipment are conducted. The author emphasizes the group of innovation enterprises in this classification. The place and role of innovation enterprises in the agrarian sector of Dnipropetrovsk region are determined.
The innovation infrastructures of Dnipropetrovsk region
Keywords: аграрні підприємства; agricultural enterprises; класифікація; classification; техніко-технологічна оснащеність; technical and technological equipment; інновації; innovations